Arm - Leg coordination profiling during the dolphin kick and the arm pull-out in elite breaststrokers - Seifert, L.; Conceição, A.; Gonjo, T.; Stastny, J.; Olstad, B. H. (Journal of Sports Sciences, 2021)
In breaststroke races, the dolphin kick could finish before, at the same time, or during the arm pull-out, but it is unclear how swimmers perform this technique. The aim of this study was to investigate whether swimmers glide between the dolphin kick and arm pull-out, favour continuity or even overlap those two phases, as it would impact the active underwater sequence. Fourteen international and national male swimmers performed 100-m breaststroke with all-out effort in a pre-calibrated 25 m swimming pool. A multi-camera system tracked the head of the swimmers. Key points of the active underwater sequence were obtained from notational analysis. A hierarchical cluster analysis identified three coordination profiles. All swimmers started their dolphin kick before the arm pull-out. However, one swimmer started the arm pull-out before the end of the dolphin kick, seven swimmers started the arm pull-out after the end of the dolphin kick, and four swimmers synchronised the beginning of the arm pull-out and the end of the dolphin kick, while two other swimmers mixed two coordination profiles among the start and the three turns. Those different profiles allow achieving similar performance outcome, suggesting individual training regarding the underwater phase.